Chromosome mapping of repetitive sequences in Anostomidae species: Implications for genomic and sex chromosome evolution - Da Silva, Edson Lourenço [UNESP]; De Borba, Rafael Splendore [UNESP]; Parise-Maltempi, Patrícia Pasquali [UNESP] (Springer Nature, 2012)
Background: Members of the Anostomidae family provide an interesting model system for the study of the influence of repetitive elements on genome composition, mainly because they possess numerous heterochromatic segments and a peculiar system of female heterogamety that is restricted to a few species of the Leporinus genus. The aim of this study was to isolate and identify important new repetitive DNA elements in Anostomidae through restriction enzyme digestion, followed by cloning, characterisation and chromosome mapping of this fragment. To identify repetitive elements in other Leporinus species and expand on studies of repetitive elements in Anostomidae, hybridisation experiments were also performed using previously described probes of LeSpeI repetitive elements. Results: The 628-base pair (bp) LeSpeII fragment was hybridised to metaphase cells of L. elongatus individuals as well as those of L. macrocephalus, L. obtusidens, L. striatus, L. lacustris, L. friderici, Schizodon borellii and S. isognathus. In L. elongatus, both male and female cells contained small clusters of LeSpeII repetitive elements dispersed on all of the chromosomes, with enrichment near most of the terminal portions of the chromosomes. In the female sex chromosomes of L. elongatus (Z2,Z2/W1W 2), however, this repeated element was absent. In the remaining species, a dispersed pattern of hybridisation was observed on all chromosomes irrespective of whether or not they were sex chromosomes. The repetitive element LeSpeI produced positive hybridisations signals only in L. elongatus, L. macrocephalus and L. obtusidens, i.e., species with differentiated sex chromosomes. In the remaining species, the LeSpeI element did not produce hybridisation signals. Conclusions: Results are discussed in terms of the effects of repetitive sequences on the differentiation of the Anostomidae genome, especially with respect to sex chromosome evolution. LeSpeII showed hybridisation patterns typical of Long Interspersed Elements (LINEs). The differential distribution of this element may be linked to sex chromosome differentiation in L. elongatus species. The relationship between sex chromosome specificity and the LeSpeI element is confirmed in the species L. elongatus, L. macrocephalus and L. obtusidens. © 2012 da Silva et al.; licensee BioMed Central Ltd.
Keywords: Chromosomes; FISH; Heterochromatin; Neotropical fish; Sex chromosomes; genomic DNA; repetitive DNA; restriction endonuclease; Anostomidae; base pairing; chromosome map; controlled study; DNA hybridization; female; fish; gene cluster; Leporinus elongatus; Leporinus friderici; Leporinus lacustris; Leporinus macrocephalus; Leporinus obtusidens; Leporinus striatus; long interspersed repeat; male; metaphase chromosome; molecular cloning; molecular evolution; molecular probe; nonhuman; priority journal; Schizodon borellii; Schizodon isognathus; sex chromosome; sex difference; sex ratio; Leporinus